Расчет предела прочности хрупких материалов с учетом внутреннего трения - Локшина, Л.Я.; Костандов, Ю.А.; Васильев, Д.Л. (Геотехническая механика, 2009)
Досліджується напружено-деформований стан зразка матеріалу при одноосному стисненні з урахуванням внутрішнього тертя матеріалу. Встановлено вплив внутрішнього тертя на опірність матеріалу зрушенню і вид траєкторії максимальних дотичних напружень.
Отримано рівняння стану матеріалу на траєкторії максимальних дотичних напружень й рівняння для розрахунку межі міцності матеріалу з урахуванням внутрішнього тертя. The stress-strain state of the sample of material at the uniaxial compression taking into account the internal friction of material is researched. Influence of internal friction on a destruction resistibility of material and an aspect of a trajectory of maximum tangential stresses is established. The equation of a state of a material on a trajectory of maximum tangential stresses and the equation for calculation of limit of material strength taking into account an internal friction is
obtained.